Double inference in the processes of comprehension of Russian and English discourse complicated by an idiom - Suvorova, Elena; Polyakova, Liliya (Penerbit Universiti Kebangsaan Malaysia, 2018)
The paper briefly surveys contemporary studies in the field of secondary nomination and idiom comprehension in discourse. The research mainly focuses on the inferential processes which occur at the moment of perceiving a discourse containing an idiom. Although the inference phenomenon has received much attention in recent years, the majority of scientific works on the topic are targeted at the inferential processes in text comprehension while such a challenging area as inference in secondary nomination remains unrevealed. The aim of the present study is to find out if the traces of inferences in the metaphoric meaning of an idiom can interfere in the comprehension of a discourse complicated by an idiom. Thus, the study presents an analysis of idiom comprehension in a narrative discourse that lies in both fields of inference study: inference in secondary nomination and inference in discourse comprehension. For this purpose, the paper gives an outline to the theories which explain some mechanisms of inference action and presents an analysis of some pieces of narrative discourse from the perspectives of the discussed theories. The research is conducted on Russian and English language material. The results of the study point to the double mapping of the inferential processes that is caused, on the one hand, by the inferential traces of secondary nomination and, on the other hand, by the implicit sense of an idiom in discourse. The paper presents a model of conceptual integration in the process of double inference while comprehending a text complicated by an idiom.